Kesadaran Kesehatan Mental Bagi Aparatur Sipil Negara - Aidar Fakhry (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Mental health is a condition in which a person has well-being as seen from himself who is able to realize his own potential, has the ability to cope with life's pressures and is normal in every situation in life, is able to work productively and productively, and is able to contribute to his community. According to the World Federation for Mental Health (World Federation for Mental Health) explains the notion of mental health as a condition that allows for good physical, intellectual and emotional development, as long as it is in accordance with the circumstances of other people. Good mental health has an inner condition that is in a peaceful, calm and positive state, so that it makes a person enjoy everyday life and respect other people around him. But on the other hand, when you have a mental health disorder, it will have an impact such as: emotions are always high and irritable and experience unexplained pain.